2006
DOI: 10.1037/1072-5245.13.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Sources of stress in policewomen: A three-factor model.

Abstract: It has been argued that models of stress need to be occupation specific. Policewomen are an occupational subgroup who experience stress differently from male officers. Sixteen sources of felt stress were rated by 206 policewomen. Exploratory factor analysis suggested a three-factor model of operational, interpersonal, and management/organizational stress. Confirmatory factor analysis with a second sample of 213 policewomen confirmed the three-factor structure. Interpersonal stressors accounted for most varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
1
23
1
2
Order By: Relevance
“…In a recent study we have found that the police profession is recognized as being an occupation involving challenging and unpredictable encounters (Backteman-Erlanson et al 2011), and a further identifying factor is organizational stress (Liberman et al 2002;Thompson et al 2006). In general, work-related stress has an impact on health and wellbeing (Paoli and Merllie 2001).…”
Section: Introductionmentioning
confidence: 95%
“…In a recent study we have found that the police profession is recognized as being an occupation involving challenging and unpredictable encounters (Backteman-Erlanson et al 2011), and a further identifying factor is organizational stress (Liberman et al 2002;Thompson et al 2006). In general, work-related stress has an impact on health and wellbeing (Paoli and Merllie 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Morash, Kwak and Haarr (2006) found that women officers reported significantly higher levels of harassment, bias, underestimation of physical abilities, and lack of influence than their male counterparts. Thompson, Kirk and Brown (2006) found that interpersonal stressors and lack of support, contributed significantly to stress levels. Haarr (1997) and Shelley, Morabito & Tobin-Gurley (2011) reported that women felt that men officers questioned their abilities to do the job.…”
Section: Introductionmentioning
confidence: 99%
“…Haarr (1997) and Shelley, Morabito & Tobin-Gurley (2011) reported that women felt that men officers questioned their abilities to do the job. Sexual harassment and discrimination are often mentioned as stressors among women officers (Deschamps et al, 2003; Thompson et al, 2006; Chaiyavej & Morash, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Morash and Haarr (1995) found that female officers experienced greater harassment and bias in their work environment despite multiple similarities between reported sources of stress in male and female police officers. Similarly, Thompson et al (2006) examined a 3-factor model of sources of perceived stress in female officers, and found that interpersonal work environment stressors (i.e., lack of support from colleagues, gender discrimination, sexual harassment, interpersonal conflict, and lack of confidentiality; Thompson et al, 2006) contributed to the largest percentage of variance in reported stress; organizational and operational stress also contributed to overall levels of stress among female officers. Despite a great deal of evidence supporting the relationship between various aspects of the work environment and PTSD symptoms, there has also been evidence to the contrary.…”
mentioning
confidence: 99%